2013
DOI: 10.1242/dev.087791
|View full text |Cite
|
Sign up to set email alerts
|

Genetic elevation of Sphingosine 1-phosphate suppresses dystrophic muscle phenotypes in Drosophila

Abstract: SUMMARYDuchenne muscular dystrophy is a lethal genetic disease characterized by the loss of muscle integrity and function over time. Using Drosophila, we show that dystrophic muscle phenotypes can be significantly suppressed by a reduction of wunen, a homolog of lipid phosphate phosphatase 3, which in higher animals can dephosphorylate a range of phospholipids. Our suppression analyses include assessing the localization of Projectin protein, a titin homolog, in sarcomeres as well as muscle morphology and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 48 publications
5
49
2
Order By: Relevance
“…Studies in Drosophila melanogaster have shown that genetic elevation of S1P (caused by the deletion of S1P lyase) suppresses dystrophic muscle phenotypes 61 . Because there are no known S1PR homologues in D. melanogaster , it was suggested that localized intracellular S1P elevation directly promotes the suppression of muscle wasting in fruitflies 61 .…”
Section: Targeting S1p Synthesis and Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in Drosophila melanogaster have shown that genetic elevation of S1P (caused by the deletion of S1P lyase) suppresses dystrophic muscle phenotypes 61 . Because there are no known S1PR homologues in D. melanogaster , it was suggested that localized intracellular S1P elevation directly promotes the suppression of muscle wasting in fruitflies 61 .…”
Section: Targeting S1p Synthesis and Degradationmentioning
confidence: 99%
“…Because there are no known S1PR homologues in D. melanogaster , it was suggested that localized intracellular S1P elevation directly promotes the suppression of muscle wasting in fruitflies 61 . Thus, it is possible that inhibitors of S1P lyase may provide a new therapeutic strategy for myopathies.…”
Section: Targeting S1p Synthesis and Degradationmentioning
confidence: 99%
“…Furthermore, increasing S1P levels by oral delivery of 2-acetyl-4(5)-tetrahydroxybutyl imidazole (THI), an inhibitor of S1P lyase (which catalyzes the irreversible degradation of S1P), also leads to suppression of dystrophic muscle degeneration in flies (Pantoja et al, 2013). In mice, administration of THI is beneficial in the recovery from acute muscle injury in the mdx dystrophic model (Loh et al, 2012; Ieronimakis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila, perturbations in sphingosine levels lead to defects in muscle development and integrity (Herr et al, 2003), while elevation of intracellular S1P levels reduces muscle wasting in flies with dystrophic muscle (Pantoja et al, 2013). In mammals, S1P affects calcium homeostasis, cell contraction and differentiation of skeletal muscle (Donati et al, 2005; Formigli et al, 2002, 2009).…”
Section: Introductionmentioning
confidence: 99%